NATURAL SCIENCE EXPERIENCES SIGNIFICANT TO ELEMENTARY SCHOOL PROGRAMS OF OUTDOOR EDUCATION. - Pike, Kenneth V. (Science Education, 1962)
The article focuses on the significance of natural science experiences to elementary school programs of outdoor education in the U.S. Natural out-of-doors is one of the broad area of experience which seems to be denied for children growing up in today's society. The need of the individual to understand his physical environment as one of the primary goals of education. Technology has depleted many natural resources. Schools should play an important role in preparing scientists to meet the present need. In today's society, cultural changes exclude natural environment as an area of experience for the child. Programs in outdoor education through the method of camping provide opportunities for direct experience learning in the total living situation. The schools are responsible for providing opportunities for children to have natural science experiences in the out-of-doors. A considerable quantity of materials have been developed as an aid to the teacher for presenting certain science and conservation steps.